Transparent electronic and photoelectric synaptic transistors based on the combination of an InGaZnO channel and a TaOx gate dielectric - Li, Yuanbo (2023)
A transparent thin film transistor (TFT) based on the combination of an InGaZnO channel and a high-κ (the dielectric constant is about 42.6) TaOx gate dielectric layer is fabricated. The TFT shows robust anticlockwise hysteresis under DC voltage sweep and synaptic behaviors (i.e., excitatory postsynaptic current, short-term memory plasticity, short-term memory to long-term memory transition, and potentiation and depression) under voltage pulse stimulus. In addition, the TFT shows high responsivity to illumination of light with various wavelengths (ultraviolet and visible light). Synaptic behaviors in response to light pulse stimuli, which could be employed in vision-based neuromorphic applications, are demonstrated. Large conductance change (Gmax/Gmin > 10) and ultra-low non-linearity (α < 0.5) of the potentiation and depression can be inspired by either gate bias pulses or photoelectric pulses with short pulse widths and small amplitudes.